Motivation and pupil behavior: Pandemic infection control in a Zimbabwe Primary School context - Chiparange, Getrude Vongai; Mapolisa, Alfred; Chiwanza, Easter (Educenter : Jurnal Ilmiah Pendidikan, 2025)
This qualitative case study addresses the critical issue of pupils' adherence to COVID-19 Infection Prevention and Control Measures (IPCM) within the educational setting, specifically at Chancellor Junior Primary School in Mutare, Zimbabwe. Understanding the role of motivation in fostering positive behavioral change is crucial for mitigating disease transmission in schools. This research sought to understand how motivation affects pupils' behavior regarding COVID-19 prevention, and to develop strategies for improving their adherence to safety measures. Data was collected through purposive sampling of 30 participants, including 20 pupils, 6 teachers, and 4 parents. Focus group discussions, semi-structured interviews, and direct observations were utilized to gather rich, contextual data. Findings indicated that pupils generally exhibited positive behavior towards handwashing, staying home when sick, and cough etiquette. However, challenges were observed concerning consistent social distancing and mask-wearing. Both intrinsic and extrinsic motivational strategies were found to significantly influence pupils' adherence to IPCM, highlighting the importance of targeted motivational interventions. The study concludes that motivation is crucial for IPCM adherence, recommending interactive education, positive reinforcement, parental involvement, peer initiatives, and resource availability. These strategies, aimed at school, government, parents, and NGOs, are essential for creating a safer learning environment during and post-pandemic.